Perencanaan Core Capability Pegawai dalam Rangka Menghadapi Era Kompetitif (Studi di Pusat Konservasi Tumbuhan Kebun Raya LIPI) - Putri Andriani Dheny, Novia; Setyowati, Endah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This research was motivated by Civil Servant Apparatus regulation whichdemanded changes in the bureaucratic system. The purpose of the research is to plan employee core capability in the skill and knowledge dimensions towards the ASN era. This type of research uses a description method with a qualitative approach. The results show that planning of employee core capability is done by analyzing organizational objectives, internal and external environment of Human Resources, forecasting Human Resources needs, and planning development strategies by merit system and knowledge management.